Taxonomic revision of the genus Elmomorphus Sharp, 1888 I. Japanese and Korean species (Coleoptera: Dryopidae) - Kodada, Ján; Selnekovič, Dávid; Jäch, Manfred A.; Goffová, Katarína; Vďačný, Peter (European Journal of Taxonomy, 2021)
The species of Elmomorphus Sharp, 1888 occurring in Japan and Korea are redescribed and illustrated: E. brevicornis Sharp, 1888 (Japan, Korea) and E. amamiensis Nomura, 1959 (Japan). The standard barcoding fragment of the mitochondrial gene coding for cytochrome c oxidase subunit I (COI) was sequenced and used together with morphological characters to delimit the taxonomic boundaries of the two species. To assess their morphometric variation, eight morphometric characters were measured and statistically evaluated using principal component analysis. The two species of Elmomorphus formed distinct and well-separated clusters in the COI tree. Their interspecific divergence is very high, ranging from 22.7 to 23.9%. On the other hand, morphometric characters, including those previously presumed to be diagnostic, overlap and per se do not allow unambiguous species identification. Reliable morphological distinguishing characters are described for males and females. Molecular data along with the morphological evidence strongly confirm the species status of E. amamiensis. An identification key to the Japanese and Korean species is provided.